INTERNATIONAL COOPERATION OF EUROPEAN UNION IN LABOR MIGRATION SPHERE IN TERMS OF GLOBALIZATION - Пак, Н. А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The article deals with the peculiarities of international cooperation of the European Union inthe sphere of labor migration in the context of globalization. The processes that occurred in the studyarea in the last century and assessed the situation observed in Europe today are analyzed. Theconsequences of migration for European countries are grounded and the reasons which promptedthe leadership of Member States for a long time to promote the flow of illegal migrants areexplained. The attention on the fact that governments must unite in order to jointly solve problemsarising in the sphere of labor migration is done.